Hepatic resection following selective internal radiotherapy in the FOXFIRE clinical trial: survival, safety, and histopathology - Virdee, PS; Winter, H; Rassam, J; Goldin, R; Wasan, HS; Sharma, RA (National Cancer Research Institute, 2018)
Colorectal cancer (CRC) commonly metastasises to the liver and is a leading cause of cancer-related death. The FOXFIRE trial compared the safety and efficacy of radiosensitising chemotherapy (OxMdG: oxaliplatin, 5-fluorouracil and folic acid) with selective internal radiotherapy (SIRT) using yttrium-90 resin microspheres (SIR-Spheres®; Sirtex Medical Limited) to OxMdG alone as first-line management for liver-dominant metastatic CRC. In patients downsized to potentially-curative hepatic resection, we explored survival, safety, and histopathological findings.